Evaluation of processed rubber seed oil Hevea brasiliensis utilization as lipid source in Clarias gariepinus feed - Nuraini Annisa; Muhammad Agus Suprayudi; Mia Setiawati; Ichsan Ahmad Fauzi (Jurnal Akuakultur Indonesia)
ABSTRACT